Ultrasound-Induced Amino Acid-Based Hydrogels With Superior Mechanical Strength for Controllable Long-Term Release of Anti-Cercariae Drug - Ling, Liying; Zhu, Lei; Li, Yibao; Liu, Chunhua; Cheng, Linxiu (Frontiers in Bioengineering and Biotechnology, 2021)
Stimuli-responsive hydrogels are significantly programmable materials that show potential applications in the field of biomedicine and the environment. Ultrasound as a stimulus can induce the formation of hydrogels which exhibit different structures' superior performance. Here, we report an ultrasound-induced supramolecular hydrogel based on aspartic acid derivative N, N'-diaspartate-3, 4, 9, 10-perylene tetracarboxylic acid imide, showing superior performance in drug release. The results show that the driving force of this ultrasonic induced hydrogel could be attributed to hydrogen bonding and π-π interaction. The rheological and cytotoxicity test illustrate excellent mechanical properties and biocompatibility of the hydrogel. The anti-Schistosoma japonicum cercariae drug release results show large drug loadings (500 mg/mL) and long-term release (15 days) of this hydrogel. This work demonstrates that this hydrogel may serve as a slow-release platform for anti-cercariae.